Snapshots - Klein, Norma (New York, N.Y. : Dial Books for Young Readers, 1984)
The lives of thirteen-year-old Sean, preparing for his bar mitzvah, his friend Marc, and their families are disrupted when the boys' interest in photography involves them in the district attorney's investigation of child pornography and kidnapping.
Keywords: Photography; Pornography; Jews -- New York (State) -- New York; Family life